2009
DOI: 10.4142/jvs.2009.10.3.181
|View full text |Cite|
|
Sign up to set email alerts
|

Isolation and characterization of canine umbilical cord blood-derived mesenchymal stem cells

Abstract: Human umbilical cord blood-derived mesenchymal stem cells (MSCs) are known to possess the potential for multiple differentiations abilities in vitro and in vivo. In canine system, studying stem cell therapy is important, but so far, stem cells from canine were not identified and characterized. In this study, we successfully isolated and characterized MSCs from the canine umbilical cord and its fetal blood. Canine MSCs (cMSCs) were grown in medium containing low glucose DMEM with 20% FBS. The cMSCs have stem ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
99
1
14

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(125 citation statements)
references
References 36 publications
11
99
1
14
Order By: Relevance
“…Therefore, one should consider the known differences in features of MSCs from different species. As in equine MSCs, CD 29 and CD 44 expressions are found consistently in canine (34,35,51,52), ovine (53), and porcine (54) MSCs. Corresponding to the equine antigen expression profile as well, CD 73 could not be detected in canine, rabbit, or sheep MSCs (35,55,56), while rat tendon derived, feline and bovine neonatal cell sources and caprine bone marrow-derived MSCs expressed this antigen (57)(58)(59)(60).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, one should consider the known differences in features of MSCs from different species. As in equine MSCs, CD 29 and CD 44 expressions are found consistently in canine (34,35,51,52), ovine (53), and porcine (54) MSCs. Corresponding to the equine antigen expression profile as well, CD 73 could not be detected in canine, rabbit, or sheep MSCs (35,55,56), while rat tendon derived, feline and bovine neonatal cell sources and caprine bone marrow-derived MSCs expressed this antigen (57)(58)(59)(60).…”
Section: Discussionmentioning
confidence: 95%
“…Until now, this remains a challenge because there are only few monoclonal antibodies (mAbs) available that show cross-reactivity with equine epitopes (30)(31)(32)(33). Moreover, it is known that there are differences in cell surface marker expression of MSCs between different species (34,35). Potentially due to these reasons, the complete marker panel proposed for human MSCs was not yet shown to be applicable to equine cells.…”
mentioning
confidence: 99%
“…Neurogenic induction was performed by culturing cells for 24 h in a preinduction media consisting of HG-DMEM, 20% FBS and 1 mM β-mercaptoethanol (Sigma) [14,20], with neural induction then performed by switching to a medium composed of DMEM plus 2% FBS, 2% dimethylsulfoxide (DMSO; Sigma) and 200 µM butylated hydroxyanisole (Sigma) for 3 days [21]. Non-induced control cells were cultured for the same time in a standard medium.…”
Section: Differentiation Assaysmentioning
confidence: 99%
“…As such, gestational tissues including umbilical cord blood (Kern et al 2006, Koch et al 2007, Guest 2008, Reed & Johnson 2008, Bartholomew et al 2009, Schuh et al 2009, Seo et al 2009, Raoufi et al 2011, umbilical cord tissues (Mitchell et al 2003, Carlin et al 2006, Hoynowski et al 2007, Cremonesi et al 2008, Passeri et al 2009, Lovati et al 2011, Iacono et al 2012a, amniotic tissues (Filioli Uranio et al 2011, Iacono et al 2012a, 2012b, Lange-Consiglio et al 2012, and amniotic fluid (AF) (Chen et al 2011, Dev et al 2011, Lovati et al 2011, Iacono et al 2012a) have been recently suggested, also in veterinary medicine, as appealing candidates for the derivation of MSCs to use in cell biotechnology. The human lesson teaches that presumptive adult stem cells derived from gestational tissues retain highest proliferation capacity, longest telomere length, broadest differentiation, and extensive proliferative potential when compared with cells obtained from adult tissues (Kogler et al 2004, Kern et al 2006.…”
Section: Introductionmentioning
confidence: 99%